The bipolar–borderline personality disorders connection in major depressive patients. (4th February 2013) - Perugi, G.; Angst, J.; Azorin, J.‐M.; Bowden, C.; Vieta, E.; Young, A. H.; ,
<x xml:space="preserve">Abstract</x> Objective The study focuses on the controversial relationship between borderline personality disorder (BPD) and bipolar disorder (BD), defined according to different criteria set, in a world‐wide sample of patients with a current major depressive episode (MDE). Method A total of 5635 patients with an MDE were enrolled in a multinational study, designed to assess varying definition of hypo/mania and familial and clinical variables associated with bipolarity. Patients with (BPD+) and without (BPD−)comorbid BPD were compared on sociodemographic, familial and clinical characteristics. Results Five hundred and thirty‐two patients (9.3%) met criteria for BPD. A diagnosis of BD was more frequent in BPD+ than in BPD− using either DSM‐IVTR‐modified criteria or the bipolar specifier. BPD+ were younger than BPD− depressives with regard to age and age at onset. They also showed more hypomania/mania in first‐degree relatives in comparison to BPD− as well as more psychiatric comorbidity, psychotic symptoms, mixed states, atypical features, seasonality of mood episodes, suicide attempts, prior mood episodes and antidepressants‐induced hypo/manic switches. Conclusion In our sample, selected on the basis of the presence of a mood disorder, the BD‐BPD connection is confirmed by the high prevalence of bipolarity in depressive patients with BPD and by the significant association with familial and clinical features classically considered as external validators of bipolarity.